Devising a Pricing Strategy for a Cloud-Based Manufacturing Start-Up: A Case Study of Co-Fabrico - Avery, A.B.S (2016)
This report set out to establish a pricing strategy for a Cloud-based Manufacturing start-up, Co-Fabrico. Based at the University of Nottingham, the company is in its nascent stages and as of yet, online trading has not yet been established. In the hope of providing some insight into competitors and understanding the concept of value, this report aims to try and quantify potential pricing options for the company. The report delves into the concept of value creation, exploring both the theory of value in an experiential manner, value from a purely economic standpoint and the notion of hedonic value. It draws attention to the growing marketplace that Co-Fabrico currently resides; it is expected to expand to $56 billion in 2018 and $131 billion by 2022. The theoretical definitions of cloud-based manufacturers are explored and applied to Co-Fabrico’s service offering. An analysis of potential competitors is presented, highlighting the functionality of their services and exploring the pricing plans that each company has on their website. An examination of Co-Fabrico’s offering is presented and considered to be unique. Its combination of ideation contests, access to the latest manufacturing technology for inventors and designers online and an ecosystem that facilitates co-creation through open innovation is unseen on any other platform that is currently offered. Potential pricing strategies are suggested for Co-Fabrico, combining both theoretical and practical justifications for their implementations. While it is acknowledged the final decisions lies with the CEO of the company, what is presented is an extensive look at what Co-Fabrico could implement when trading begins. Cost-plus pricing and value-pricing are considered in a tiered-subscription pricing plan manner. Overall, it is concluded that there is not enough information presented to the report to provide a conclusive pricing plan or strategy. It is noted that more financial information is needed to provide a long-term strategy that would suit Co-Fabrico. Furthermore, the combination of services that Co-Fabrico offers makes it difficult to provide one overall pricing plan, and so it is necessary to consider each offering on an individual basis. There is however some justified suggestions that could be implemented once other administrative activity in other areas of the company has been completed. If chosen, it would be of interest to view how the plans evolve over time, and whether they do attract a significant consumer base for Co-Fabrico.